Anterior cruciate ligament biomechanics during robotic and mechanical simulations of physiologic and clinical motion tasks: A systematic review and meta-analysis. Issue 1 (January 2015) - Bates, Nathaniel A.; Myer, Gregory D.; Shearn, Jason T.; Hewett, Timothy E.
Abstract Investigators use in vitro joint simulations to invasively study the biomechanical behaviors of the anterior cruciate ligament. The aims of these simulations are to replicate physiologic conditions, but multiple mechanisms can be used to drive in vitro motions, which may influence biomechanical outcomes. The objective of this review was to examine, summarize, and compare biomechanical evidence related to anterior cruciate ligament function from in vitro simulations of knee motion. A systematic review was conducted (2004 to 2013) in Scopus, PubMed/Medline, and SPORTDiscus to identify peer-reviewed studies that reported kinematic and kinetic outcomes from in vitro simulations of physiologic or clinical tasks at the knee. Inclusion criteria for relevant studies were articles published in English that reported on whole-ligament anterior cruciate ligament mechanics during the in vitro simulation of physiologic or clinical motions on cadaveric knees that were unaltered outside of the anterior-cruciate-ligament-intact, -deficient, and -reconstructed conditions. A meta-analysis was performed to synthesize biomechanical differences between the anterior-cruciate-ligament-intact and reconstructed conditions. 77 studies met our inclusion/exclusion criteria and were reviewed. Combined joint rotations have the greatest impact on anterior cruciate ligament loads, but the magnitude by which individual kinematic degrees of freedom contribute to ligament loading during in vitro simulations is technique-dependent. Biomechanical data collected in prospective, longitudinal studies corresponds better with robotic-manipulator simulations than mechanical-impact simulations. Robotic simulation indicated that the ability to restore intact anterior cruciate ligament mechanics with anterior cruciate ligament reconstructions was dependent on loading condition and degree of freedom examined.